Understanding SME’s failure – focus on success factors and gender differences: comparative analysis of SME’s in Czech Republic, Hungary and Serbia - Majlath, Melinda; Kelemen-Erdős, Anikó; Valocikova, Cyntia (Serbian Journal of Management, 2019)
In the last three decades women has started to conquer the business world – there are more and more women entrepreneurs all over the world. However, their proportion among business leaders is still much lower than their proportion in the society. In the EU, policy-makers pay special attention to women’s businesses – especially in the SME sector. Doing business is by default a risky activity and failure or financial difficulty is almost a natural part of it. Learning from hard times and from the experiences of others may help entrepreneurs to create better strategies to survive. The aim of this paper is to highlight factors and reasons for financial distress, in order to provide ideas how to prevent these difficulties. The research conducts 329 entrepreneurs who suffered from financial distress previously in the Czech Republic, Hungary and Serbia via online survey. There are not any significant differences in perceiving financial difficulties regarding gender. However, there are slight differences among countries, mainly in entrepreneurial factors.